Pengaruh Keselamatan Kerja, Kesehatan Kerja, Dan Jaminan Sosial Terhadap Kinerja Karyawan Pada PT. Bukit Angkasa Makmur Di Bengkulu Tengah - Ardi, Sandi; Wiliamin, Janusi; Army, M. Noor (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study aims to examine the influence of occupational safety, occupational health, and social security on employee performance at PT. Bukit Angkasa Makmur in Central Bengkulu. The sampling technique used in this research was purposive sampling, and data were collected through questionnaires. The total sample consisted of 84 employees. The research employed a quantitative approach. The results revealed that the independent variables—occupational safety, occupational health, and social security—simultaneously have a positive and significant effect on the dependent variable, employee performance. Furthermore, each independent variable also showed a positive and significant partial effect on employee performance. Data analysis was conducted using multiple linear regression with the aid of SPSS software. The findings indicate that improving occupational safety through the provision of personal protective equipment and a secure work environment, enhancing occupational health systems, and ensuring transparent and adequate social security measures can directly improve employee productivity. Therefore, it is recommended that the company continues to strengthen policies and practices in these three areas to support optimal performance. This study is expected to serve as a reference in human resource management, particularly in efforts to enhance performance through improved employee welfare.